PEMBERDAYAAN KELOMPOK CAGAR BUDAYA KALIPASIR MELALUI OPTIMALISASI POTENSI BERBASIS DIGITAL - Winandari, Maria Immaculata Ririk; Setiadi, Virginia Suryani; Wijayanto, Punto; Hartono, Ebenezer Emanuel; Rahmad, Dafa Al (Jurnal AKAL: Abdimas dan Kearifan Lokal, 2025)
The community around the Cultural Heritage Area plays an important role in preservation efforts. One of the cultural heritage sites in Tangerang City is the Kalipasir Mosque and Cemetery. Engaging the community through tour guides is one way to involve them in these activities. This community group empowerment initiative aims to enhance the skills of the Kalipasir Cultural Heritage group and increase the number of tour guides capable of explaining the history and uniqueness of this heritage site. The method used is participatory training, which includes narrative development and tour guide training. The Cultural Heritage group is invited to participate in crafting the cultural heritage narrative and designing tourism routes. The outcomes of this community service program include tourism products such as an Instagram social media account, an infographic map, booklets, postcards, and fans, as well as publications in the form of journal articles, electronic media, videos, and posters. The implications of this PkM program, beyond increasing the number of tour guides, also strengthen the sense of ownership within the Kalipasir Cultural Heritage group.